Trends of domestic violence against women in China: an age-period-cohort analysis - Shen, Hui; Xie, Yongxiang (Frontiers in Public Health, 2025)
ObjectiveDomestic violence (DV) against women is a worldwide public health problem. This study explored the dynamics of DV in China from 1990 to 2010.MethodsBased on nationally representative data from the 1990, 2000, and 2010 China Women's Social Status Survey (CWSS) involving 29,995 women, we employed the Hierarchical APC-Cross-Classified Random Effects Models (HAPC-CCREM) to disentangle the effects of age, period and cohort on DV trends.ResultsThe reported overall prevalence of DV substantially declined from 26.7% in 1990 to 5.4% in 2010. The decline was more pronounced in rural areas (from 31.9 to 7.8%) than in urban areas (from 21.4 to 3.2%). The highest prevalence of reported violence occurred among women aged 30–34. However, among rural women, the risk increased with age. The period effect revealed a consistent decline in women's risk of DV over time, with rural areas showing a faster reduction than urban areas. The cohort effect indicated a significant decrease in risk for women born between 1976 and 1990 compared to earlier cohorts. Among urban women, the risk remained relatively stable across cohorts, whereas rural women experienced a marked decline.ConclusionsOverall, the risk of DV against women showed a downward trend. Distinct age, period, and cohort effects were observed, with a higher risk among women aged 30–34 and a lower risk among those born after 1975. The disparity in DV risk between urban and rural women narrowed over time and across birth cohorts. These patterns may be linked to broader shifts such as anti-domestic violence legislation, public health education, and improvements in women's socio-economic status.